Applications and usability of interactive TV : Third Iberoamerican Conference, jAUTI 2015, and 6th Congress on Interactive Digital TV, CTVDI 2015, Palma de Mallorca, Spain, October 15-16, 2015, revised selected papers /: Third Iberoamerican Conference, jAUTI 2015, and 6th Congress on Interactive Digital TV, CTVDI 2015, Palma de Mallorca, Spain, October 15-16, 2015, revised selected papers. (2016) - Unknown
No abstract available